2020
DOI: 10.1007/s10877-020-00460-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of lung and heart in predicting successful weaning in mechanically ventilated neurosurgical patients

Abstract: In critically ill neurosurgical patients, delayed and premature extubation increases the risk of morbidity and mortality. Assessment of critically ill patients before and during spontaneous breathing trial (SBT) is crucial in predicting weaning failure. We explored the trend of changes with integrated lung and cardiac ultrasonography in predicting success of weaning in neurosurgical patients. Lung ultrasound and cardiac ultrasound was performed before and after 30 min and 120 min of SBT. Lung ultrasound score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(46 reference statements)
0
2
0
1
Order By: Relevance
“…LUS imaging employed to ascertain patient readiness to undergo an SBT has produced conflicting results in non-COVID-19 patients. In critically ill neurosurgical patients, a high LUS score prior to a 1-h SBT conducted using a T-tube was associated with a higher risk of SBT failure [ 102 ]. Conversely, data from a bi-center, prospective, observational investigation, carried out in a heterogeneous population of 250 ready-to-wean patients, showed that B-line predominance prior to sustaining a T-tube SBT lasting 30–120 min was a very weak predictor of SBT outcome, with 47% sensitivity, 64% specificity, a positive predictive value of 25%, and a negative predictive value of 82% [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…LUS imaging employed to ascertain patient readiness to undergo an SBT has produced conflicting results in non-COVID-19 patients. In critically ill neurosurgical patients, a high LUS score prior to a 1-h SBT conducted using a T-tube was associated with a higher risk of SBT failure [ 102 ]. Conversely, data from a bi-center, prospective, observational investigation, carried out in a heterogeneous population of 250 ready-to-wean patients, showed that B-line predominance prior to sustaining a T-tube SBT lasting 30–120 min was a very weak predictor of SBT outcome, with 47% sensitivity, 64% specificity, a positive predictive value of 25%, and a negative predictive value of 82% [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…A ultrassonografia da função pulmonar, além do raio-X tradicional, consegue avaliar alguns parâmetros respiratórios, como a PEEP, analisando o trabalho dos músculos respiratórios. Isso é possível ao realizar o exame 30 minutos antes e após o TRE (SACHIN S, et al, 2021).…”
Section: Discussionunclassified
“…Ultrasonography can be valuable for assessing the function of the diaphragm during this delicate clinical phase. Sachin et al[ 39 ] studied weaning of neurosurgical patients by evaluating the performance of the lung and heart in a standardized manner. They computed a lung ultrasound score derived from the estimation of four ultrasound lung aeration patterns ranging from a normal aeration to consolidation [ 40 ].…”
Section: Lung Ultrasound Of Diaphragmatic Function and In Weaning Fro...mentioning
confidence: 99%